The impact of real effective exchange rate on revealed comparative advantage and trade balance of Pakistan - Muhammad Siddique; Ahsan Anwar; Muhammad Abdul Quddus (Universitas Islam Indonesia, 2020)
This study estimates the effects of devaluation and appreciation of real effective exchange rate (REER) on revealed comparative advantage (RCA) at Harmonized System 2-digit level of exports in Pakistan. A non-linear Autoregressive Distribute Lag (ARDL) technique is applied to test the asymmetric evidence. This study employs two models to explore the export performance. Findings/Originality: The results of model 1 estimation confirm the proof of asymmetric ARDL and concludes that devaluation has a positive effect on selected RCA’s index value and helps enhance exports of Pakistan. Meanwhile, the appreciation of REER is having an adverse impact. Model-2 estimates the effect of these selected RCA’s, REER, and world aggregated income (Yw) on the trade balance (TB) of Pakistan. The results estimate that an increase in selected RCA’s index values, world aggregated income, and REER depreciation is useful to decrease in deficit TB of Pakistan.